Leading complementary schools as non-profit social entrepreneurship: Cases from Lithuania. (October 2020) - Melnikova, Julija
The article explores the topic of leading complementary schools as models of non-profit social enterprises, reflecting the way the sector has developed in Lithuania. Complementary schools in Lithuania provide educational services often related to language and cultural education focusing on different groups such as minorities, immigrants and people with disabilities. They use client-focused activities to achieve social goals and maintain financial self-sufficiency. Therefore, the leadership of these organizations is of major importance. Group discussions were conducted with 32 heads of complementary schools to explore their perceptions of the entrepreneurship competencies they need to meet the challenges they face in establishing and sustaining their non-profit organizations. Viewing complementary schools as non-profit social enterprises and their leaders as social entrepreneurs contributes to the understanding of them as organizations and the wide range of competencies and practices needed to lead such schools effectively with implications for pre-service and in-post leadership development.